The international foundation directory - Hodson, H V. (London : Europa Publications, 1986)
The Europa International Foundation Directory provides an unparalleled guide to the foundations, trusts, charitable and grant-making NGOs, and other similar not-for-profit organizations of the world. It provides a comprehensive picture of third sector activity on a global scale.
Includes index.
Includes bibliographical references: p. 387-389.
ne 26/10/2021
Ref.
Keywords: Endowments